Quests for glory - Chainani, Soman (Chainani, Soman. School for Good and Evil, 2018)
After defeating the School Master, the students at the School for Good and Evil must take on an even bigger challenge. In order to graduate, they must complete the fourth-year "Quest for Glory," which could be the turning point in the path for either heroism or obscurity. Agatha and Tedros set a quest to return Camelot to its former glory while Sophie decides to mold evil in her own image. But as their classmates' quests cause mass chaos, someone must step in to create order and get the forces of good and evil working with each other for the common good.